Voluntary Work in Digital Contexts as Gift Exchange - Caroline Ruiner (MDPI AG, 2021)
Digital technologies have inspired a change in volunteering in nonprofit organizations. In this context, the engagement of volunteers is mainly self-organized, through online platforms or apps. It is the aim of this paper to analyze the volunteers’ motives, differentiating between self-interest and other-interest. This is important, since effects on organizational volunteer-related outcomes, such as volunteer engagement, recruitment and retention, are likely to occur. A gift exchange perspective is applied and a case study has been used for investigating an online-based nonprofit organization in Germany, consisting of qualitative interviews with experts and volunteers, documentary analysis and participatory observations as well as an online survey. The results show that the volunteers’ instrumental self-interest in gaining food, and their interests in other factors, such as the reduction of food wastage as a societal goal, occur simultaneously. This leads to paradoxes and problems on the organizational level. This study contributes to understanding volunteer engagement, recruitment and retention in digital nonprofit organizations.